Midwives' experiences regarding recordkeeping during intrapartum care in Limpopo Province healthcare facilities - Phogole C. Maesela; Johanna M. Mathibe-Neke (AOSIS, 2024)
Background: South Africa has experienced an increase in litigations because of poor recordkeeping. The quality of maternal healthcare necessitates quality recordkeeping. All midwives' interventions should be documented in the maternity case record as an instrument to highlight the quality of intrapartum care offered. Objectives: The purpose of the study was to determine and describe the experiences of midwives regarding recordkeeping during intrapartum care in Limpopo province and to make recommendations to improve recordkeeping. Method: A qualitative, explorative and descriptive design was adopted. Midwives were selected purposively to participate in focus group discussions. Data were thematically analysed with the help of the independent transcriptionist and coder. Results: The findings revealed the themes: perceptions of midwives regarding recordkeeping and the challenges and enablers that influence recordkeeping during intrapartum care. Conclusion: Quality recordkeeping requires timely, detailed, comprehensive and accurate recording. The study recommended the availability of updated guidelines, in-service training, monitoring and evaluation of recordkeeping, peer review, record auditing, proper time management among midwives and appointment of staff in line with the staffing needs of the unit to enhance recordkeeping. Contribution: Quality recordkeeping has a positive impact on the provision of quality healthcare to mothers during intrapartum care and reduces litigations related to maternity cases.